Effect of Empowerment, Work Environment and Fatigue on Silver Craft Productivity - Irwanto, Jesi (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2020)
The survival and growth of a company are not only determined by the strength of capital or money, but also determined by its success in managing human resources. The productivity of human resources is influenced by several factors. This study aims to examine the effect of empowerment, work environment and fatigue which are partially and simultaneously significant on the productivity of silver craftsmen. Respondents in this study consisted of 40 silver craftsmen in Pulo Village, Lumajang Regency. By using the analysis of multiple linear regression, the results obtained that empowerement does not have a significant effect, while the work environment and fatigue have a significant effect on productivity. The limitation of this study is limited to respondent which is only examines silver craftsmen in Pulo Village, Lumajang Regency. Hopefully, the limitation of this study can be examined in the further studies.